Muhammad Ali : a tribute to the greatest / Thomas Houson; penerjemah, Eka Saputra, Khanifah Rini Nurul Badariah; penyunting, Wisnu Prasetya Utama, Ary Koes - HAUSER, THOMAS; Eka Saputra; Khanifah; RINI NURUL BADRIYAH; Wisnu Prasetya Utama; Anif Koes (Bentang, 2016)
348 hlm. ; 20 cm.